Pulse Contour Cardiac Output System Monitoring in Pediatric Patients Undergoing Orthotopic Liver Transplantation - Ersoy, MD, Zeynep; Ozdemirkan, Zeliha Aycan; Zeyneloglu, Pinar; Cekmen, Nedim; Torgay, Adnan; Kayhan, Zeynep; Haberal, Mehmet (International Journal of Innovative Research in Medical Science, 2022)
Background: This study aimed to demonstrate that PiCCO monitoring can be early guidance for fluid monitoring and hemodynamic parameter analysis in the pediatric OLT population. Method: A single-centre, retrospective cohort study in pediatric patients who underwent OLT between September 2014 and October 2017. Results: Forty-one pediatric patients (aged 4 months to 17 years) underwent hemodynamic monitoring with PiCCO during OLT. Measurements including mean arterial pressure (MAP), central venous pressure (CVP) and cardiac index (CI) were significantly lower during the Tanhepatic phase when compared to Tbaseline and Tnewhepatic phases (p<0.05 for all). Among the patients whose mean of Tnewhepetic extravascular lung water index (EVLWI) measurements were more excellent than 7 mL/kg; more significant amounts of intraoperative blood transfused (p=0.027), higher graft recipient body weight ratio (GRWR) (p=0.016) and longer anesthesia times (p=0.046) were seen. The mean of Tnewhepatic stroke volume variability (SVV) measurements was greater than 10% in patients with a higher GRWR (p=0.033). More blood transfusion was needed and a higher GRWR was observed in patients with a global end-diastolic volume index (GEDVI)<650 ml/m2 (p=0.000). The patients with a mean of Tnewhepatic CI measurements less than 3 L/min/m2 received more colloid transfusion and had longer anesthesia time during OLT. There was a statistically significant relationship between cell-saver/kg use and hospitalisation (p=0.008), and an association between urine output and mortality (p=0.024). Conclusion: PiCCO monitoring provides flow and dynamic parameters which predict fluid responsiveness and make critical therapeutic decisions to restore hemodynamic stability in pediatric patients undergoing OLT.